Developing Essential Understanding of Statistics for Teaching Math in Grades 9-12 - Peck, Roxy (National Council of Teachers of Mathematics, 2013)
How does a statistical model differ from a mathematical model? What are the differences among the sample distribution, the sampling distribution, and the population distribution? In an experiment, what effect does the sampling method have on the results? What are the implications of the use of processes of random selection and random assignment? Can a small sample yield accurate estimates of population parameters?This book examines five big ideas and twenty-four related essential understandings for teaching statistics in grades 9-12. The authors distinguish mathematical and statistical models,